Measurement of the diffractive cross section in deep inelastic scattering using ZEUS 1994 data - Breitweg, J; Derrick, M; Krakauer, D; Magill, S; Mikunas, D; Musgrave, B; Repond, J; Stanek, R; Talaga, R; Yoshida, R; Zhang, H; Mattingly, M; et al. (1999)
The DIS diffractive cross section, dσdiffγ*p→XN/dMx, has been measured in the mass range Mx < 15 GeV for γ*p c.m. energies 60 < W < 200 GeV and photon virtualities Q2 = 7 to 140 GeV2. For fixed Q2 and Mx, the diffractive cross section rises rapidly with W, dσdiffγ*p→X N (Mx, W, Q2)/dMx ∝ Wadiff with adiff = 0.507 ± 0.034 (stat) +0.155-0.046 (syst) corresponding to a t-averaged pomeron trajectory of ̄αℙ = 1.127 ± 0.009 (stat) +0.039-0.012 (syst) which is larger than ̄αℙ observed in hadron-hadron scattering. The W dependence of the diffractive cross section is found to be the same as that of the total cross section for scattering of virtual photons on protons. The data are consistent with the assumption that the diffractive structure function FD(3)2 factorizes according to cursive greek chiℙFD(3)2(cursive greek chiℙ, β, Q2) = (cursive greek chi0//cursive greek chiℙ)nFD(2)2(β, Q2). They are also consistent with QCD based models which incorporate factorization breaking. The rise of cursive greek chiℙFD(3)2 with decreasing cursive greek chiℙ and the weak dependence of FD(2)2 on Q2 suggest a substantial contribution from partonic interactions.